In vitro protective effects of an aqueous extract of Clitoria ternatea L. flower against hydrogen peroxide‐induced cytotoxicity and UV‐induced mtDNA damage in human keratinocytes. (21st February 2018) - Zakaria, N.N.A.; Okello, E.J.; Howes, M‐J.; Birch‐Machin, M.A.; Bowman, A.
Abstract : The traditional practice of eating the flowers of Clitoria ternatea L. or drinking their infusion as herbal tea in some of the Asian countries is believed to promote a younger skin complexion and defend against skin aging. This study was conducted to investigate the protective effect of C. ternatea flower water extract (CTW) against hydrogen peroxide‐induced cytotoxicity and ultraviolet (UV)‐induced mitochondrial DNA (mtDNA) damage in human keratinocytes. The protective effect against hydrogen peroxide‐induced cytotoxicity was determined by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium assay, and mtDNA damage induced by UV was determined by polymerase chain reaction. Preincubation of HaCaT with 100, 250, and 500 μg/ml CTW reduced cytotoxicity effects of H2 O2 compared with control (H2 O2 alone). CTW also significantly reduced mtDNA damage in UV‐exposed HaCaT ( p  < .05). CTW was chemically‐characterized using high resolution liquid chromatography–mass spectrometry. The main compounds detected were assigned as anthocyanins derived from delphinidin, including polyacylated ternatins, and flavonol glycosides derived from quercetin and kaempferol. These results demonstrated the protective effects of C. ternatea flower extracts that contain polyacylated anthocyanins and flavonol glycosides as major constituents, against H2 O2 and UV‐induced oxidative stress on skin cells, and may provide some explanation for the putative traditional and cosmetic uses of C. ternatea flower against skin aging.